2018
DOI: 10.1039/c8ra05057k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance and microbial community successional patterns in an integrated OCO reactor under ZnO nanoparticle stress

Abstract: An integrated OCO reactor was used to investigate the performance and microbial community successional changes under a long-term exposure to relatively low-level ZnO nanoparticles (NPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Proteobacteria, one of the dominant bacterial phyla, showed a decreasing trend in most treatment (Table S6). Likewise, previous studies have reported that abundance of Proteobacteria decreased under stress from the M-NPs (e.g., ZnO and Fe 0 NP) in OCO reactor and landfill leachate (Liu et al, 2018;Shi et al, 2019). The trend of Actinobacteria changes was similar to ARGs changes, such as sul1, aac(6')-Ib, and ermB, which implies that Actinobacteria may have been responsible for the increasing trend of ARG in the samples.…”
Section: Discussionsupporting
confidence: 61%
“…Proteobacteria, one of the dominant bacterial phyla, showed a decreasing trend in most treatment (Table S6). Likewise, previous studies have reported that abundance of Proteobacteria decreased under stress from the M-NPs (e.g., ZnO and Fe 0 NP) in OCO reactor and landfill leachate (Liu et al, 2018;Shi et al, 2019). The trend of Actinobacteria changes was similar to ARGs changes, such as sul1, aac(6')-Ib, and ermB, which implies that Actinobacteria may have been responsible for the increasing trend of ARG in the samples.…”
Section: Discussionsupporting
confidence: 61%